Technical, environmental and economical evaluation of three types of treatment for lettuce growing in vegetables gardens, in Santa María de Guácimo, Limón, Costa Rica - Ramírez-Ramírez, Fiorella (2016)
Tecnológico de Costa Rica has developed collaborative actions with the Guácimo local Government (Limón province, Costa Rica) through research and a doctoral thesis. As a follow-up, another research and extension project was proposed, called Establishment of vegetables home gardens using solid waste in a pilot group in the Santa María de Guácimo community. This project carried out activities like the analysis of prior sudies regarding solid waste generation and composition in the community, as well as trials of different types of treatment for biodegradable solid waste through composting. The graduation project named Technical, environmental and economical evaluation for three lettuce treatments from home food-gardens in Santa María de Guácimo, Limón, Costa Rica” joined in support to the objectives of the first one. Since Guácimo’s Municipality faces monetary challenges to manage its wastes, the proposal of treating biodegradable solid wastes through domestic composting and using that compost in home gardening seemed to be an adequate option. Therefore,  the evaluation in purpose of the study mention above became relevant.  The Takakura composting method, the MM composting method and the  commercial compost and a trial witness were applied in lettuce gardens. After analyzing the results in terms of mass, diameter, cost and environmental opportunities, they showed that although the Takakura composting method had a higher cost, it could produce wider environmental and economic benefits.